The Relationship between Knowledge, Sickness Period, and Intraocular Pressure to the Quality of Life of Glaucoma Patient - Efifta Pratama Ananda (Universitas Airlangga, 2016)
Based on data from Indonesia basic health research (Riskesdas) in 2008, the national prevalence of glaucoma was 0.5%. Glaucoma is the second leading cause of blindness after cataracts that are permanent or irreversible so that glaucoma patients must take continuous treatment. This research was conducted to determine the relationship between knowledge, duration of illness, and intraocular pressure on the quality of life of glaucoma patients. This research was an observational analytic study using a cross-sectional design study. The sample in this study were patients with primary glaucoma and secondary glaucoma who were treated at Mata Undaan Hospital Surabaya, which were selected using a systematic random sampling of 68 people. Data collection was carried out by interviewing glaucoma patients and based on medical records. Data processing using Chi-Square test analysis. The results showed that there was a relationship between knowledge (p = 0.033) and duration of illness (p = 0.035), whereas intraocular pressure was not related (p = 0.317) with the quality of life of glaucoma patients at Mata Undaan Hospital in Surabaya. The conclusion of this study is that knowledge and duration of illness are related to the quality of life of glaucoma patients, whereas intraocular pressure is not related to the quality of life of glaucoma patients. The advice that can be given is to increase knowledge of glaucoma patients, one of them is by taking regular medication to improve the quality of life.